2022
DOI: 10.3389/fphys.2022.930353
|View full text |Cite
|
Sign up to set email alerts
|

Development of High Fat Diet-Induced Hyperinsulinemia in Mice Is Enhanced by Co-treatment With a TLR7 Agonist

Abstract: Metabolic syndrome (MetS) is common in Systemic Lupus Erythematosus (SLE) patients and is associated with increased cardio-renal risk. Toll-like receptor 7 (TLR7) stimulation promotes the development of SLE through mechanisms including activating type I Interferon (IFN) and autoreactive B cells. The current study tested whether combined TLR7 agonist treatment and exposure to a high fat, high sucrose “Western diet” intervention affects the early-stage development of SLE or MetS features. Female C57BL/6 mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 54 publications
3
2
3
Order By: Relevance
“…Not only are TLRs known for their role in innate immunity, but a role in the progression of obesity‐related inflammation and metabolic complications has also emerged. The current study, as well as recent work by our group (Kakalij et al., 2022 ) and others (Hanna Kazazian et al., 2019 ; Revelo et al., 2016 ) suggest that enhanced TLR7 activation may exacerbate the development of MetS features, including impaired glucose homeostasis and insulin resistance. We report that pharmacological TLR7 activation promoted impairment of glucose tolerance in female FVB/N mice exposed to a HFD for 12 weeks.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Not only are TLRs known for their role in innate immunity, but a role in the progression of obesity‐related inflammation and metabolic complications has also emerged. The current study, as well as recent work by our group (Kakalij et al., 2022 ) and others (Hanna Kazazian et al., 2019 ; Revelo et al., 2016 ) suggest that enhanced TLR7 activation may exacerbate the development of MetS features, including impaired glucose homeostasis and insulin resistance. We report that pharmacological TLR7 activation promoted impairment of glucose tolerance in female FVB/N mice exposed to a HFD for 12 weeks.…”
Section: Discussionsupporting
confidence: 76%
“…C57BL/6 mice are regarded as susceptible to developing MetS when placed on a hypercaloric diet (Leonardi et al, 2020). We did not detect a significant independent effect of IMQ on FVB/N fasting blood glucose in the current study at either 6 or 12 weeks, whereas there was a significant increase in C57BL/6J mice at 6 weeks (Kakalij et al, 2022), perhaps reflecting strain differences in the response to HFD. Revelo et al reported that 8 days of IMQ treatment impaired glucose tolerance but did not raise fasting blood glucose in male C57BL/6 mice maintained on a normal control diet (Revelo et al, 2016).…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations